2001
DOI: 10.1046/j.1463-1318.2001.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure after repair of rectovaginal fistula in Crohn’s disease: analysis of prognostic factors

Abstract: Closure of a RVF in Crohn's disease should not be considered an easy undertaking, especially in patients with several Crohn's sites. In this very heterogeneous group of patients the technique is adapted to the nature and the extent of accompanying anorectal disease. Construction of a temporary stoma is not mandatory and can be limited to complex cases. Healing can be obtained in 75% of all patients, although a late recurrence might occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
1
25
0
14
Order By: Relevance
“…Rectovaginal fi stulas associated with Crohn's disease tend to have higher recurrence rates than those due to other etiologies [ 22 , 72 ]. Among those with Crohn's, the number of sites involved with Crohn's has also been found to be associated with outcome [ 73 ], although another study found no association between Crohn's activity and failure [ 26 ]. Thus, endorectal advancement fl ap can certainly be used in an attempt to heal rectovaginal fi stulas associated with Crohn's disease, but success rates are low.…”
Section: Rectovaginal Fistula Associated With Crohn's Diseasementioning
confidence: 99%
“…Rectovaginal fi stulas associated with Crohn's disease tend to have higher recurrence rates than those due to other etiologies [ 22 , 72 ]. Among those with Crohn's, the number of sites involved with Crohn's has also been found to be associated with outcome [ 73 ], although another study found no association between Crohn's activity and failure [ 26 ]. Thus, endorectal advancement fl ap can certainly be used in an attempt to heal rectovaginal fi stulas associated with Crohn's disease, but success rates are low.…”
Section: Rectovaginal Fistula Associated With Crohn's Diseasementioning
confidence: 99%
“…Penninckx et al [11] konnten drei Risikofaktoren für die Abheilung von M.-Crohn-Fisteln herausarbeiten. Sowohl in der uni-als auch in der multivariaten Analyse wurde die Anzahl der zusätzlichen M.-Crohn-befallenen Darmabschnitte als wichtiger prognostischer Faktor identifiziert.…”
Section: Enterovesikale Fistelnunclassified
“…Sowohl in der uni-als auch in der multivariaten Analyse wurde die Anzahl der zusätzlichen M.-Crohn-befallenen Darmabschnitte als wichtiger prognostischer Faktor identifiziert. In der univariaten Analyse konnten zudem die Präsenz eines zusätzlichen M. Crohn und die Anzahl vorangegangener Fistelverschlüsse als Risikofaktoren charakterisiert werden [11]. …”
Section: Enterovesikale Fistelnunclassified
“…2 Primary repair of RVF is associated with a wide success rate that ranges from 45% to 70%. 1,[3][4][5] When CD is associated, RVF becomes a challenging complication; a number of surgical procedures tend to be unsuccessful and have a high initial failure rate (50%). Therefore, healing can be obtained only after subsequent attempts in two-thirds of patients, with successful stoma closure in 75%.…”
mentioning
confidence: 99%
“…Therefore, healing can be obtained only after subsequent attempts in two-thirds of patients, with successful stoma closure in 75%. [5][6][7] Various surgical options have been suggested for RVF repair. These include (from simple to more complex procedures): direct repair, fistulotomy, fibrin glue instillation, endorectal or vaginal advancement flap, abdominal procedures with colorectal or coloanal anastomosis, and epiplooplasty.…”
mentioning
confidence: 99%